(In)visible women: a narrative study of larger women's pregnant embodiment and maternal healthcare - Chowdhry, Sushila (The University of Edinburgh, 2019)
The research on which this thesis is based explores larger women’s experience of ‘maternal obesity’. My work takes a social constructionist approach to studying experience. This approach has been criticised for privileging the social aspects of embodiment at the expense of the more material, visceral aspects. My contribution addresses this criticism by adopting a novel narrative approach to the study of embodied experience. To do so I draw on writing from the fields of medical sociology, anthropology and bioethics, along with feminist and critical social perspectives to theorise the body as social, cultural, political and lived. At the heart of my work is the desire to examine, in detail, aspects of the ‘moral jeopardy’ (Murphy, 1999) which larger pregnant women have encountered in healthcare spaces and to explore the ways current obstetric approaches to ‘maternal obesity’ shape larger women’s experiences of pregnant embodiment. By doing so, I make a contribution to knowledge about how the changing embodied experience of pregnancy is shaped by maternal healthcare practices in the context of maternal obesity discourse. The research is based on repeat in-depth interviews with six women who were medically classified as having ‘maternal obesity’. The women were recruited from a single Scottish maternity hospital during the early stages of their pregnancies. The women’s experience of pregnancy and childbirth was captured in three interviews over the course of their pregnancy and following childbirth. In order to gain a better understanding of the context in which the women received their care, individual face-to- face narrative interviews were also conducted with key maternal health professionals including five obstetricians, six midwives, and two anaesthetists. Data were analysed using a two-stage structural narrative analysis involving identifying how and why particular stories were told in the course of interviews, and exploring the broader narratives drawn on to make meaning in these stories. Following the work of sociolinguist Gee (1999, 2011), particular attention was paid to the ways that characters, situations, actions, and artefacts were framed in the stories. These framings revealed how participants understood their own actions, and those of others, in the context of their stories of experience. The research findings are presented as a series of composite monologues following the journey women travel through maternal healthcare - from the early stages of pregnancy through to the postnatal period. Presenting the findings in this way illuminates how the context of maternal healthcare configures pregnant embodiment as the pregnancy advances. Each monologue is accompanied by a commentary discussing the main analytical points, engaging with existing literature, and discussing the findings in light of what is known and the contribution made by this research. The findings reveal the complexities of maternal healthcare professional positionality in relation to the larger pregnant body, shaping the practice of these professionals with regard to larger embodiment. The findings further demonstrate that larger women’s highly stigmatised and visible bodies render them vulnerable to targeted medical screening which also stigmatises the foetal body. Moreover, this process can serve to silence the women by rendering them somewhat (in)visible.
Keywords: maternal obesity; women’s experience; social aspects; maternal healthcare practices; maternal obesity discourse; in-depth interviews